Rosario+Vampire. Season II. 10 - Ikeda, Akihisa, 1976- (Shonen Jump advanced., 2012)
Tsukune has three problems: the other boys at Monster High want to get rid of him because they are jealous of his popularity with the girls, and most of the girls also want to kill him because he only pays attention to the vampire girl, Moka. She has strong feelings for Tsukune ... she thirsts for his blood.